Creating an inclusive social studies classroom for exceptional learners - Minarik, Darren; Lintner, Timothy (Emerald Publishing Limited : Information Age Publishing, Inc., 2024)
"Creating an Inclusive Social Studies Classroom for Exceptional Learners serves as a comprehensive reference guide for K-12 educators and university-based social studies methods instructors and special education instructors wanting to create more inclusive opportunities for students with disabilities in the general education curriculum. Numerous research-based methods and instructional strategies are shared that enable teachers to effectively engage all learners in the social studies classroom. Social studies educators are encouraged to become a leading voice in support for the inclusion of students with disabilities in K-12 general education classrooms. Written by scholars with extensive backgrounds in social studies and special education, this book enhances and extends the small but growing body of literature addressing the needs of students with disabilities in social studies classrooms. Divided into three sections, the chapters explore how social studies provides an opportunity to create more inclusion for students with disabilities, how to create an inclusive learning environment through best practices in collaborating and planning, and how to help students with disabilities gain access to social studies content and achieve higher levels of understanding. Each chapter provides a brief theoretical underpinning and the latest research within the chapter topic, and practical and engaging strategies that readers can easily implement within their own classrooms. Educators receive guidance on how to get started with implementing the strategies along with suggestions for future research topics"--